TINGKAT KEPUASAN WAJIB PAJAK DI KANTOR PELAYANAN PAJAK PRATAMA SEMARANG TIMUR (STUDI KASUS PELAYANAN PAJAK PENGHASILAN) - Ivana Rantansari; Herbasuki Nurcahyanto (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2018)
Every citizen who have income, should report their income, wealth, and debt through SPT. One of the tax offices in Semarang is Tax Office of East Semarang. The aim of this research is to knowing the other dimensions of the taxpayer’s satisfaction. This research method using the quantitative descriptive, and using the validity test and reliability test, also using the Importance Performance Analysis (IPA) for the analysis tool. The method of the collecting data are questionnaire and interview. The result of the research is that the level of performance of the employees are lower than the level of expectation. It can be seen from the processing result and the level of performance is 3,27, and the level of expectation is 3,56. According to the level of performance and expectation, the result of the percentage is 91,85% and belongs to satisfied. The recommendation of this research is the employees should do the education and training to fix the empathy and attitude dimensions so that will increasing the satisfaction of the taxpayers.